A Neuroanatomical Framework for Upper Limb Synergies after Stroke - McMorland, Angus J. C.; Runnalls, Keith D.; Byblow, Winston D. (Frontiers in Human Neuroscience, 2015)
Muscle synergies describe common patterns of co- or reciprocal activation that occur during movement. After stroke, these synergies change, often in stereotypical ways. The mechanism underlying this change reflects damage to key motor pathways as a result of the stroke lesion, and the subsequent reorganization along the neuroaxis, which may be further detrimental or restorative to motor function. The time course of abnormal synergy formation seems to lag spontaneous recovery that occurs in the initial weeks after stroke. In healthy individuals, motor cortical activity, descending via the corticospinal tract (CST) is the predominant driver of voluntary behaviour. When the CST is damaged after stroke, other descending pathways may be up-regulated to compensate. The contribution of these pathways may emerge as new synergies which take shape at the chronic stage after stroke, as a result of plasticity along the neuroaxis. The location of the stroke lesion, and properties of the secondary descending pathways and their regulation are then critical for shaping the synergies in the remaining motor behaviour. A consideration of the integrity of remaining descending motor pathways may aid in the design of new rehabilitation therapies.